Pregnancy outcomes following ultrasound-guided high-intensity focused ultrasound in submucous leiomyomas: a retrospective study - Dacheng Qu; Yue Liu; Jing Jiang; Qiuling Shi; Honggui Zhou; Zhibiao Wang (International Journal of Hyperthermia, 2023)
AbstractObjective To investigate the impact of ultrasound-guided high-intensity focused ultrasound (USgHIFU) on pregnancy in submucous leiomyomas.Materials and methods Between October 2015 and October 2021, a retrospective observational study was conducted at the Affiliated Hospital of North Sichuan Medical College, China, for 32 women with submucous leiomyomas who became pregnant after USgHIFU. Pregnancy outcomes, submucous leiomyomas characteristics, and USgHIFU parameters were analyzed.Results A total of 17 (53.1%) deliveries were successfully achieved, with full-term delivery in 16 (94.1%) patients and preterm delivery in 1 (5.9%). After USgHIFU, the effective volume in the uterus cavity and the volume of submucous leiomyomas shrank in all 32 patients. The median time to achieve pregnancy after USgHIFU was 11.0 months. Before pregnancy, myoma type was downgraded in 13 (40.6%) patients, stable in 10 (31.3%) and upgraded in 9 (28.1%). The vaginal expulsion rate of submucous leiomyomas was 28.1%, with complete expulsion in 3 (9.4%) patients and partial expulsion in 6 (18.8%). After USgHIFU, the size of submucous leiomyomas did not increase in each trimester (all p > 0.05). The high complications rate during pregnancy (7/17, 41.2%) was associated with advanced maternal age, with only one (5.9%) premature rupture of membranes possibly associated with submucous leiomyomas. There were 6 (35.5%) vaginal delivery and 11 (64.7%) cesarean sections. All 17 newborns developed well, with a mean birth weight of 3482 g.Conclusions In patients with submucous leiomyomas, pregnancies and full-term deliveries can be successfully achieved following USgHIFU, with few related complications.